Integrated Coastal Management in Latin America: the ever New World - Scherer,Marinez (2014)
The advancement of Integrated Coastal Zone Management (ICZM) in Latin American countries may vary from established programs to experimental phase implementation and even inexistence. This creates an opportunity for the development of new ideas and experiments, especially in the quite long stretches of littoral where no occupation has yet been planned or consolidated. However there are localized issues that need to be attended with certain degree of urgency, especially in coastal settings that have been urbanized, developed for industry and/or are situated around port facilities. Spain and Portugal implemented the marine and environmental policies of European Union and may be seen as models for public and private ICZM initiatives. These situations created opportunities and needs that are somehow reflected in dedicated scientific production, as well as in social impact and the related capacity building programs. We surveyed some key costal management journals to know how Latin American based academics are doing in their mission of creating, developing and discussing ICZM along our diverse shores stretching along all climatic zones. Capacity building programs and exchange networks were also scrutinized. Results suggest that the thematic participation in the major publication channels is modest and needs to improve in number and diversity of subjects bringing obvious benefits to the policy and decision makers. Capacity building programs are still in its infancy across the region. There are no, or very few, specialized educational programs to form practitioners and scientists at all academic levels. Training programs integrating countries around all aspects of ICZM are even scarcer. Coordinated actions, such as networks across the political borders are one of the many future needs we point out here as being the next frontier for thinkers and managers in the region.